Scope of Spirituality Research in Occupational Therapy Literature: A Scoping Review Study - Masoud Babaei; Mehdi Rassafiani (مجله پژوهش در علوم توانبخشی, 2017)
Introduction: Spirituality leads people to seek for life meaning and life purpose. Occupational therapy (OT) is a holistic profession that believes all of experienced aspects of human including physical, psychological, social and spiritual aspects are important to the health of human being. However, the general consensus is that occupational therapy literature has not paid enough attention to the concept of spirituality. Therefore, purpose of this article was to present the extent and nature of research about spirituality in that occupational therapy and finding gaps in this area.